ANALISIS KRITIS VISUALISASI GAME COOKING MAMA DALAM KONTEKS IDEOLOGI DAN SIMULASI - MIKI TJANDRA (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2016)
Cooking Mama is a famous cooking simulation game which can be played in a variety of mobile platforms and smartphones. The game introduces players to the world of cooking in a virtual environment. The visualization of gaming, especially the characters and objects in the game, exposing some interpolation of ideological perspectives through the images to generate specific meanings. The players follow the instructions of a lead character named ‘Mama’ and do an array of kinesthetic activities of ‘cooking’ in a simulation, which is in the form of the abstraction of real cooking activities. This essay analyzes the critical context of ideology and simulation in the Cooking Mama game. Keywords: character; cooking; ideology; simulation; visual